Terrorism, Economic Downturns and Elections - Javier Gardeazabal (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
Within EUSECON, one research subproject investigates the relationship between economic downturns, terrorism and electoral outcomes. The analysis is carried out using data from Spain. Recent Spanish democratic history has witnessed four complete economic cycles, with deep recessions and pronounced booms. During this period, there has been a nationalistic conflict with terrorist manifestation. This research uses Spanish provincial data from the ten congressional elections since the end of Franco's dictatorship. It has been found that changes in unemployment, inflation and terrorism significantly influence national vote shares.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330